Placental lesions in patients with antiphospholipid antibody syndrome: experience of a single tertiary-care Italian reference center - Canti, Valentina; De Lorenzo, Rebecca; Inguscio, Giulia; Girardelli, Serena; Pozzoni, Mirko; Tenace, Nazario Pio; Lucianò, Roberta; Pasi, Federica; Castiglioni, Maria Teresa; Cavoretto, Paolo Ivo; Rovere-Querini, Patrizia (Frontiers in Lupus, 2024)
Introduction. Abnormal placentation contributes to obstetric morbidity in antiphospholipid antibodies syndrome (APS). The placenta is the main target of antiphospholipid antibodies (aPL) in obstetric APS and is the site of dysfunctional inflammatory responses and thrombosis.Standard treatment for APS during pregnancy includes low-dose aspirin (LDA) plus low molecular weight heparin (LMWH) and, in refractory cases, hydroxychloroquine (HCQ).Recently, a systematic review of the literature identified five main pathological placental lesions in APS patients: placental infarction, decidual vasculopathy, decidual inflammation, increase of syncytial knots due to syncytiotrophoblast death, and decrease in vasculosyncytial membranes. The aims of this study were to investigate whether placental lesions associate with obstetrical outcomes in a cohort of APS patients.Obstetrics Outpatient Clinic of San Raffaele Hospital, Milan, were enrolled. Placental samples from 25 spontaneously conceived pregnancies in APS patients were collected from January 2017 to May 2023 and analyzed.Results. All (n=130) patients were on LDA and 110/130 (85%) on both LDA and LMWH.Twenty-six patients (20%) also received HCQ. In these patients, signs of placental inflammation (preterm birth and preterm premature rupture of membranes) were less frequently observed. Of the 25 placental samples analyzed, 19 (76%) patients had primary APS, while 6 patients had APS secondary to SLE. All patients were treated with LDA and LMWH. In patients with concomitant systemic lupus erythematosus (SLE) or in refractory APS, HCQ was added. Histological analysis of placental tissue revealed increased syncytial knots in 17/25 (68%) placentas, decreased vasculosyncytial membranes in 11/25 (44%), infarction in 8/25 (32%), presence of macrophages and decidual inflammation in 2/25 (8%), and atherosis or reduction of spiral artery remodeling in 3/25 (12%). We also observed at least two coexisting placental lesions in 12/25 (48%) placentas. In the placenta of patients treated with HCQ we did not observe any decidual inflammation at histology.Placental anomalies have occurred in patients with APS despite close and optimal obstetric monitoring. It is thus tempting to speculate that HCQ may have beneficial effects on pregnancy by decreasing the risk of deciduitis in patients with APS.